C–F-rich oil drop as a non-expendable fluid interface modifier with low surface energy to stabilize a Li metal anode. Issue 6 (19th May 2021) - Yang, Qifan; Hu, Jiulin; Meng, Junwei; Li, Chilin
Abstract : A strategy for non-expendable fluid interface modification is proposed by interposing a C–F-rich PFPE oil drop with a low surface energy onto a Li metal anode to address the problem of deformation. Abstract : Metallic Li is currently the most promising anode material for use in next-generation batteries in the pursuit of higher energy densities. However, its uncontrollable electro-deposition can result in unstable breakage of the solid electrolyte interphase (SEI) and severe dendrite growth, hindering the commercialization of Li metal batteries (LMBs). Here, a strategy for non-expendable fluid interface modification is proposed by interposing a C–F-rich oil drop (perfluoropolyether, PFPE) with a low surface energy to address the deformation of the Li anode. Different from usual additives, which disperse in the electrolyte and are sacrificed during cycling, this laminated oil drop can endurably protect the Li anode from a side reaction with the electrolyte and mitigate Li-salt consumption. Its high fluidity and inertness enable the 'dynamic' healing of 'hot-spots' without the compromise of Li + permeability and Li nucleation kinetics. The PFPE moieties close to the Li skin trigger the interface enrichment of the C–F and Li–F components to reinforce the robustness of the SEI and the compactness of the Li plating (from mosaic-tile-like packing to a dense interconnected network). This strategy endows LiNi0.8 Mn0.1 Co0.1 O2 /Li full cells with an ultralong cycling life (over 700 cycles) and an ultrahigh rate endurance (up to 10C). This study provides a novel route to high-performance LMBs based on immiscible liquid interlayers as a permanent modulator.